Socio-Economic Impact Analysis on the "SAY" Convection Business in Gresik - Amirah Salma Achmadi; Abdur Rohman (Public Service: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study aims to analyze the socio-economic impact of the existence of the “SAY” uniform convection business in Gresik on the surrounding community and workers. This small business is considered to have a strategic role in creating a balance between economic growth and improving social welfare. The method used is qualitative descriptive research, with data collection through in-depth interviews and documentation studies. The results of the study indicate that this business has an economic impact in the form of job creation, increasing employee income, and encouraging local economic activity. From a social perspective, this business improves the quality of life of employees, especially women, and shows social concern through an orphan assistance program. This study underlines the importance of the existence of MSMEs in socio-economic development at the local level and the need for ongoing support so that its benefits can be felt more widely.